Between coordination and regulation: Finding the governance in Internet governance - Jeanette Hofmann; Christian Katzenbach; Kirsten Gollatz (New media & society, 2017)
Following recent theoretical contributions, this article suggests a new approach to finding the governance in Internet governance. Studies on Internet governance rely on contradictory notions of governance. The common understanding of governance as some form of deliberate steering or regulation clashes with equally common definitions of Internet governance as distributed modes of ordering. Drawing on controversies in the broader field of governance and regulation studies, we propose to resolve this conceptual conundrum by grounding governance in mundane activities of coordination. We define governance as reflexive coordination – focusing on those `critical moments', when routine activities become problematic and need to be revised, thus, when regular coordination itself requires coordination. Regulation, in turn, can be understood as targeted public or private interventions aiming to influence the behaviour of others. With this distinction between governance and regulation, we offer a conceptual framework for empirical studies of doing Internet governance.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; coordination; economics of convention; governance; ICANN; Internet Governance Forum; intentionality; Internet governance; ordering; reflexive coordination; regulation